Mobile Learning Is A Future Learning Trend Based On Smartphones - David Darwin (PT. Anagata Sembagi Education, 2025)
The development of digital technology has brought significant changes to the world of education, one of which is through mobile learning (mlearning). Mlearning allows learning to take place flexibly, overcome the limitations of space and time, and is adjusted to the individual's learning rhythm. In Indonesia, the adoption of mlearning is increasingly relevant after the COVID19 pandemic, with smartphones as the main device used. Based on APJII data (2023), more than 70% of internet users in Indonesia access the internet via smartphones, showing the great potential of mlearning for the future of education. However, the implementation of mlearning faces challenges such as the gap in access to technology and low digital literacy. Mlearning also encourages a personalized learning paradigm, where students can access materials that suit their needs and learning styles. AI-based applications, microlearning, and gamification make it easier to create a contextual and adaptive learning experience. However, the challenges of managing the quality of materials and equitable access need to be overcome. This study uses a descriptive qualitative approach through a literature study to understand the development of mlearning and its challenges. It is hoped that the integration of this technology can support more inclusive and sustainable education, with an important role for education policies, teacher training, and increasing digital literacy among students.